Astrocytes and neurons share region-specific transcriptional signatures that confer regional identity to neuronal reprogramming - Herrero-Navarro, Alvaro; Puche-Aroca, Lorenzo; Moreno-Juan, Veronica; Sempere-Ferrandez, Alejandro; Espinosa, Ana; Susin, Rafael; Torres-Masjoan, Laia; Leyva-Diaz, Eduardo; Karow, Marisa; Figueres-Onate, Maria; Lopez-Mascaraque, Laura; Lopez-Atalaya, Jose P.; et al. (Science Advances, 2021)
Neural cell diversity is essential to endow distinct brain regions with specific functions. During development, progenitors within these regions are characterized by specific gene expression programs, contributing to the generation of diversity in postmitotic neurons and astrocytes. While the region-specific molecular diversity of neurons and astrocytes is increasingly understood, whether these cells share region-specific programs remains unknown. Here, we show that in the neocortex and thalamus, neurons and astrocytes express shared region-specific transcriptional and epigenetic signatures. These signatures not only distinguish cells across these two brain regions but are also detected across substructures within regions, such as distinct thalamic nuclei, where clonal analysis reveals the existence of common nucleus-specific progenitors for neurons and astrocytes. Consistent with their shared molecular signature, regional specificity is maintained following astrocyte-to-neuron reprogramming. A detailed understanding of these regional-specific signatures may thus inform strategies for future cell-based brain repair.
CRIS-Team Scopus Importer:2021-04-19